Importance Des Produits Forestiers Non Ligneux Medicinaux D’origine Vegetale Et Impacts Des Activites Anthropiques Sur Leur Durabilite Dans Le Sud-Ouest De La Republique Centrafricaine - Guy Gildas Zima; Fidèle Mialoundama; Jean Michel Yangakola; Innocent Kossa (European Scientific Journal, ESJ, 2018)
The forest in the south-west of the Central African Republic has enormous potential for non-timber forest products (NTFPs) of plant origin. The objective of this study is to identify the medicinal value of these NTFPs of plant origin with high health potential and the effects of human activities on their sustainability. The study was carried out in 09 villages in the intervention zone of the Kadéi Forestry Company. From various methodological approaches (ethno botanical survey, participant observation, inventory technique), data were collected, processed and analysed. From the results obtained 91 non-wood medicinal plant species belonging to 29 families and to one large systematic group, the Magnoliophytes were identified. These species represent a means of therapeutic remedies used by 91% of surveyed populations to treat many diseases, symptoms and infections. Tree barks (43.26%) and leaves (39.21%) are the most commonly harvested organs. The variables collected related to the types of uses allowed to identify 19 priority NTFPs medicinal and underline the process of degradation of 7 important NTFPs. This degradation is mainly due to the way in which the natural resource is harvested, causing a large number of non- woody medicinal plant species to become rare. The definition of strategies based on ecological and socioeconomic harvesting techniques of NTFPs are solutions to ensure sustainable management of these products for the benefit of future generations.